Esoteric Interpretation of the Quran in "The Study Quran": A New Translation and Commentary (2015) by Seyyed Hossein Nasr et al. - Riza, Zikri (Al-Bayān, 2023)
The fundamental objective of this research is to explicate the uniqueness of esoteric interpretation in The Study Quran: A New Translation and Commentary (2015) written by Seyyed Hossein Nasr and his team. This library research applies qualitative research methods and an interdisciplinary approach, that is Sufism science. The result unveils that esoteric interpretation tradition in the contemporary era tries not to reduce the esoteric meaning of the Quran to Sufism authority and that every individual has the possibility to interact with the Quran’s esoteric meaning. The uniqueness of moderate esoteric interpretation in The Study Quran helps find new meanings of the Quran as a contemporary perspective in interpreting a text.